Is Indonesia Stock Exchange Semi-Strong Form Efficiency? - Nelmida Nelmida (Jurnal Manajemen, 2020)
This study aims to analyze the effect of the announcement of warrant listing on the stock price movement on the Indonesia Stock Exchange (IDX). The data used in this study is secondary data on companies that warrant listing from 2011 to 2018. The number of samples used is 10 with a purposive sampling technique. The analysis technique used in this study is the study of events, by using ten windows before and after the warrant listing. To prove the hypothesis proposed by conducting a t-statistic test. Based on the results of the analysis it was found that there were significant differences an abnormal returns and cumulative abnormal returns before and after the announcement date of the warrant listing on the Indonesia Stock Exchange, and it could be indicated that the Indonesia Stock Exchange was called the semi-strong form efficiency.